2020
DOI: 10.21203/rs.3.rs-19417/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General and Tuberculosis-Specific Service Readiness in two states in Nigeria

Abstract: Background : Tuberculosis is the world’s deadliest infectious disease and a leading cause of death in Nigeria. The availability of a functional healthcare system is critical for effective TB service delivery and attainment of national and global targets. This study was designed to assess readiness for TB service delivery in Oyo and Anambra states of Nigeria. Methods: This was a facility-based study with a mixed-methods convergent parallel design. A multi-stage sampling technique was used to select 42 prima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…30 A recent study done in Oyo and Anambra states of Nigeria found that up to 80% of facilities had TB treatment guidelines. 31 Another study done in Tanzania found that 70% of all facilities did have TB diagnosis and treatment guidelines. 32 Although direct comparison cannot be made given that both primary and non-primary health facilities were included in these studies, the difference highlights the important need for equipping PHCs with simple, comprehensive and easy to use TB diagnosis and treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 A recent study done in Oyo and Anambra states of Nigeria found that up to 80% of facilities had TB treatment guidelines. 31 Another study done in Tanzania found that 70% of all facilities did have TB diagnosis and treatment guidelines. 32 Although direct comparison cannot be made given that both primary and non-primary health facilities were included in these studies, the difference highlights the important need for equipping PHCs with simple, comprehensive and easy to use TB diagnosis and treatment guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Anambra and Oyo states of Nigeria, less than 24% of health workers were trained on MDR-TB across multiple healthcare levels. 31 Given the fact that MDR-TB is one of the major drivers of global TB epidemic, there is need for its inclusion in the current training package for PHC workers. Such a move will likely improve their ability to provide holistic TB care including TB infection prevention and control, MDR-TB detection, patient-centred treatment needs and disease surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…They can also focus more on developing a comprehensive assessment involving other elements influencing the success of TB treatment, such as drug surveillance to prevent inappropriate use and nonadherence, diagnosis, and equity of access to the medicine. This comprehensive assessment is helpful to strengthen the TB-related health system in LMICs, which is currently still weak (32).…”
mentioning
confidence: 99%